Limited genetic diversity found among genotypes of the Entada landrace (Ensete ventricosum, (Welw.) Chessman) from Ethiopia - Haile, Alye Tefera; Kovi, Mallikarjuna Rao; Johnsen, Sylvia Sagen; Hvoslef-Eide, Trine; Tesfaye, Bizuayehu; Rognli, Odd Arne (Frontiers in Plant Science, 2024)
The Entada landrace of enset (Ensete ventricosum (Welw.) Chessman) is probably the most unique indigenous crop in Ethiopia, being maintained and utilized by the Ari people in the South of Ethiopia. Here we describe genetic diversity, selection signatures and relationship of Entada with cultivated and wild enset using 117 Entada genotypes collected from three Entada growing regions in Ethiopia (Sidama, South and North Ari). A total number of 1,617 high-quality SNP markers, obtained from ddRAD-sequences, were used for the diversity studies. Phylogenetic analysis detected a clear distinction between cultivated enset, Entada and wild enset with Entada forming a completely separated clade.However, extremely short branch lengths among the Entada genotypes indicate very little molecular evolution in the Entada lineages. Observed and expected heterozygosities were high, 0.73 and 0.50, respectively. Overall, our results strongly indicate that the Entada genotypes we have studied originated from one or a few clonal lineages that have been propagated and spread among farmers as clones. Prolonged clonal propagation of heterozygous genotypes from a single or few founding lineages has led to populations with very little or no diversity between genotypes, and high heterozygosity within genotypes. Signatures of directional selection were identified at eight loci based on an FST outlier analysis. Four candidate genes detected are involved in axillary shoot growth and might be involved in controlling natural sucker formation in Entada.